2019
DOI: 10.1111/irel.12232
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Minimum Wages on Low‐Skilled Immigrants’ Wages, Employment, and Poverty

Abstract: Raising the minimum wage has been advanced as complementary policy to comprehensive immigration reform to improve low‐skilled immigrants’ economic well‐being. While adverse labor demand effects could undermine this goal, existing studies do not detect evidence of negative employment effects. We re‐investigate this question using data from the 1994 to 2016 Current Population Survey and conclude that minimum wage increases reduced employment of less‐educated Hispanic immigrants, with estimated elasticities of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…Lastly, while studies have found that the minimum wage is ineffective in combatting current poverty, there may be intergenerational impacts that have not been accounted for in studies to date (Burkhauser & Sabia, 2007;Churchill & Sabia, 2019). Specifically, if there are academic and emotional benefits from heightened amounts of enriching time and primary childcare with children by low education parents, this could increase the probability that these children escape the intergenerational poverty cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, while studies have found that the minimum wage is ineffective in combatting current poverty, there may be intergenerational impacts that have not been accounted for in studies to date (Burkhauser & Sabia, 2007;Churchill & Sabia, 2019). Specifically, if there are academic and emotional benefits from heightened amounts of enriching time and primary childcare with children by low education parents, this could increase the probability that these children escape the intergenerational poverty cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The same study was also backed up by Churchill and Sabia (2019). They studied the minimum wage of immigrants with limited skills and its effect on poverty rates.…”
Section: Wage (W)mentioning
confidence: 99%
“…Firstly, negative employment effects associated with minimum wage increases can offset hourly wage gains (Caliendo et al, 2017;Churchill and Sabia, 2019). Secondly, minimum wage workers are spread across the household income distribution, often in high income households (Logue and Callan, 2016;MaCurdy, 2015), and these workers are typically not the primary household earner (Maitre et al, 2017).…”
Section: Introductionmentioning
confidence: 99%